Identity composition of traditional malay house compounds in rural Melaka, Malaysia - Ani, Anisa (2011)
The Malay landscape is a complex and unique architectural concept,relying on its own identity formation characteristics. It is created from a harmonious interaction between man, nature and culture. Rapid urbanization and industrialization, especially in the 1960‟s, caused massive migration, turning many traditional villages into sub-urban areas and industrial cities. Sadly, insufficient amount of efforts by the government are unable to preserve the cultural landscape of these places. Cultural landscape identification such as the Malay landscapes requires full observation and understanding of the interrelationship foundation between the social and cultural influences. Hence, the aim of the study is to investigate the physical composition of Malay landscape characteristics within rural traditional residential gardens, by understanding the influence of social and cultural factors. Literatures on social and cultural landscapes of the Malays and their background done along with the available exploration assessment methods. This study employs multiple case studies as tools and the modified Layer Cake Relationships helps to relate and analyze on-site data collection variables. Macro and micro analysis inspired from the method has resulted significant characteristics that represented the essences of the Malay identity in traditional residential compound. At the end of the research, the important highlights presented are the social and cultural identity values and threats identified at studies case which is the landscape composition and also cultural customs. This study hopefully is able to seek a better understanding of traditional Malay house gardens identity composition in Melaka, through the perspective of the house owner‟s strengths and preferences. By doing so, in aids in lengthening the character‟s life span so that it can be inherited and appreciated by our future generation.